Investigation of resonant polarization radiation of relativistic electrons in gratings at small angles; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 201, iss. 1 : Radiation from Relativistic Electrons in Periodic Structures (RREPS '01) - Aleinik A. N. Aleksandr Nikonorovich; Chefonov O. V.; Kalinin B. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Saruev G. A. Gennady Alekseevich; Sharafutdinov A. F. (2003, 2003)
Title screen